2018
DOI: 10.1055/s-0038-1649340
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Index: A Noninvasive Tool for Clinical Decision in Neonates with Suspected Sepsis?

Abstract: Aim This article aims to assess whether perfusion index is significantly different in infants with positive C-reactive protein and/or positive cultures compared with a control group. Methods This was a prospective observational cohort study. Perfusion index was evaluated in 80 neonates at the start of antibiotic therapy for suspected sepsis. Antibiotic therapy was started based on the antenatal history or the presence of clinical signs of sepsis such as hypo/hyperthermia, feed intolerance, lethargy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In the current study comparing 148 neonates with proven/probable sepsis and 126 no‐sepsis, we observed comparable PI values in the two groups except that the neonates with proven/probable sepsis had significantly lower PI values in three time‐epochs (0–6 h, 31–36 h and 49–54 h) than neonates with no‐sepsis. These findings are in sync with the published literature 11,12,14 . The neonates born to mothers with histological chorioamnionitis had significantly lower PI values at 1 and 5 min of life than normal neonates 11,12 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the current study comparing 148 neonates with proven/probable sepsis and 126 no‐sepsis, we observed comparable PI values in the two groups except that the neonates with proven/probable sepsis had significantly lower PI values in three time‐epochs (0–6 h, 31–36 h and 49–54 h) than neonates with no‐sepsis. These findings are in sync with the published literature 11,12,14 . The neonates born to mothers with histological chorioamnionitis had significantly lower PI values at 1 and 5 min of life than normal neonates 11,12 .…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in sync with the published literature. 11,12,14 The neonates born to mothers with histological chorioamnionitis had significantly lower PI values at 1 and 5 min of life than normal neonates. Interestingly, non-survivors had significantly lower PI values even at the baseline.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations